Decoding Movement From Electrocorticographic Activity: A Review - Volkova, Ksenia; Lebedev, Mikhail A.; Kaplan, Alexander; Ossadtchi, Alexei (Frontiers in Neuroinformatics, 2019)
Electrocorticography (ECoG) holds promise to provide efficient neuroprosthetic solutions for people suffering from neurological disabilities. This minimally invasive recording technique combines an adequate temporal and spatial resolution with the lower risks of medical complications compared to the other invasive methods. ECoG is routinely used in clinical practice for preoperative cortical mapping in epileptic patients. During the last two decades, the number of studies utilizing ECoG has considerably grown, including the paradigms where behaviorally relevant information is extracted from ECoG activity with various signal processing algorithms. Several research groups have advanced toward the development of assistive devices driven by brain-computer interfaces (BCIs) that decode motor commands from multichannel ECoG recordings. Here we review the principles of operation of such BCIs and discuss the potential areas for their future development.